Demystifying the past: mythical subversion in Herminio Martínez' novel Diario maldito de Nuño de Guzmán. - Andzel-O'Shanahan, Edyta (Amaltea. Revista de Mitocrítica, 2022)
This article offers a myth-critical analysis of the novel Diario maldito de Nuño de Guzmán by Herminio Martínez, published in 1990. Firstly, arguments supporting the application of the term «myth» to the narrative of the Spanish Conquest of America, which emerged from early colonial historiography, will be presented. Subsequently, the analysis of the subversive character of Martinez' novel will be provided. In particular, the strategies of demythification on the story level and demythologisation on the discourse level will be examined in detail. The article is intended as a contribution to the myth-critical methodology and praxis.
Keywords: myth; Conquest of America; subversion; demythification; demythologisation